Rhetorical Reading for Writing Strategies - Kuzborska, Irena (University of Muhammadiyah Prof. DR. HAMKA, 2019)
This article is based on the plenary talk given at the inaugural UHAMKA International Conference on English Language Teaching (ELT) and Computer Assisted Language Learning (CALL) (UICELL 2018) in Jakarta, Indonesia, 23 November 2018, and focuses on the explanation of reading as a communicative rhetorical act. Outlining the key features of such reading, it then considers the benefits of reading texts rhetorically. A specific focus is given to the role of rhetorical reading in writing. While the article acknowledges the limited research on the relationship, it provides some evidence that reading texts rhetorical can lead to both more effective reading and more effective writing. A specific technique on how to teach students to read texts rhetorically is also presented in this article.